Caspase‐mediated cleavage and DNase activity of the translation initiation factor 3, subunit G (eIF3g). Issue 22 (27th September 2013) - Kim, Jong-Tae; Lee, Seon-Jin; Kim, Bo-Yeon; Lee, Chul-Ho; Yeom, Young Il; Choe, Yong-Kyung; Yoon, Do-Young; Chae, Suhn-Kee; Kim, Jung Woo; Yang, Young; Lim, Jong-Seok; Lee, Hee Gu
Abstract : Eukaryotic translation initiation factor 3 is composed of 13 subunits (eIF3a through eIF3m) and plays an essential role in translation. During apoptosis, several caspases rapidly down‐regulate protein synthesis by cleaving eIF4G, ‐4B, ‐3j, and ‐2α. In this study, we found that the activation of caspases by cisplatin in T24 cells induces the cleavage of subunit G of the eIF3 complex (eIF3g). The cleavage site (SLRD 220 G) was identified, and we found that the cleaved N‐terminus was translocated to the nucleus, activating caspase‐3, and that it also showed a strong DNase activity. These data demonstrate the important roles of eIF3g in the translation initiation machinery and in DNA degradation during apoptosis. Abstract : eIF3g is cleaved at SLRD 220 G by caspase‐3 and ‐7 during apoptosis. The cleaved N‐terminus of eIF3g translocates to the nucleus. The N‐terminus of eIF3g exhibits DNase activity.